Analisis Manajemen Pelayanan Kesehatan dalam Meningkatkan Kualitas Pelayanan di Puskesmas Pembantu Meri Kota Mojokerto - Nabila Luthfi Talitha; Zahra Syety Yuda Aulia; Annida Qonita Syahida; Ratu Andini Anindiya Hanum; Trenda Aktiva Oktariyanda; Meirinawati (Jurnal Pelita Nusantara, 2026)
Health services are one of the important forms of public service in fulfilling the basic needs of society. Research on health service management at the Auxiliary Community Health Center (Puskesmas Pembantu) level is still relatively limited, even though this facility plays an important role in providing community health services at the local level. This study aims to analyze health service management in improving service quality at Puskesmas Pembantu Meri, Mojokerto City. The study employed a descriptive qualitative approach with data collection techniques consisting of interviews, observations, and literature review. The results showed that the service management at Puskesmas Pembantu Meri has been implemented quite well through the application of online and offline registration systems, queue management, referral systems, flexible workforce allocation, and periodic service evaluations. This study also found that the digitalization of services through the JKN Mobile application helped improve service efficiency and reduce patient queues. However, the implementation of digital-based services has not been fully optimal due to limited technological literacy among some members of the community. In addition, the high targets of health programs and digital-based reporting obligations potentially increase the administrative burden on health workers. Therefore, the quality of health services is influenced not only by the service system itself, but also by the effectiveness of human resource management, organizational coordination, and the ability to adapt to technology-based service transformation.